The clinicodemographic characteristics and outcome of patients with renal colic - Regmi, Prabodh; Dutta Subedi, Dharma; Singh Gurung, Narayan (Journal of Chitwan Medical College, 2024)
Background: Kidney stone disease is important urological condition. This study aims analyse clinico-demographic characteristics and outcome of patients with renal colic, presenting in Emergency Department. Method: This was a prospective observational study conducted from 15 Jan 2024 to 14 Jun 2024 in the Department of Urology and Department of Emergency, Rapti Academy of Health Sciences, Dang, Nepal. Ethical approval was obtained. Microsoft Excel and Statistical Package for the Social Sciences (SPSS) were used for descriptive analysis of clinicodemographic characteristics parameters such as age, sex, renal colic symptoms, size of stones, hydronephrosis; and outcome variables such as conservative or surgical management. The Chi-square test / Fisher's extract test was used for association. A p-value of <0.05 was considered statistically significant. Result: Among 156 patients, renal colic was most commonly observed in the age group 20-29 years in 79(50.5%) patients with male to female ratio of 1.05:1, flank pain in 148(94.8%) followed by nausea in 128(82.1%). The history of stone disease was recorded in 36(23%) cases. Stone was located in the lower ureter in 56(35.9%) and in vesico-ureteric junction in 51(32.6%) cases. Surgical management was required in 15(9.6%) cases. Hydronephrosis was observed in 145(93%) patients. Nonsteroidal anti-inflammatory drug was primarily used as an analgesic. Opioid was needed in 14(9%) cases. Conclusion: Renal colic was most common in the younger age group (20-30 years). Spontaneous passage of stone was common, and only a minority (9.6%) needed surgery.